Reaction-bonded silicon carbide for nuclear fusion blanket applications - Leide, A (2019)
Reaction-bonded silicon carbide has properties which make it useful for certain components of a nuclear fusion reactor, but its response to irradiation has not been studied since early work suggested its unsuitability. Modern commercially available samples of RB-SiC, along with some novel samples prepared in-house were investigated to identify links between microstructure and radiation and mechanical performance.